2021
DOI: 10.1016/j.clae.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

BCLA CLEAR – Contact lens technologies of the future

Abstract: Contact lenses in the future will likely have functions other than correction of refractive error. Lenses designed to control the development of myopia are already commercially available. Contact lenses as drug delivery devices and powered through advancements in nanotechnology will open up further opportunities for unique uses of contact lenses.This review examines the use, or potential use, of contact lenses aside from their role to correct refractive error. Contact lenses can be used to detect systemic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 441 publications
(632 reference statements)
0
28
0
5
Order By: Relevance
“…Contact lenses have been widely used by millions of people worldwide for decades for vision correction [ 5 ]. They are biocompatible, safe, durable and comfortable, thus providing a new route for ophthalmic drug delivery [ 6 ]. Numerous animal studies demonstrated that ophthalmic medications delivered by therapeutic contact lenses could prolong the time a drug stays on the cornea and increase its bioavailability by at least 50%, compared with eye-drop formulations [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contact lenses have been widely used by millions of people worldwide for decades for vision correction [ 5 ]. They are biocompatible, safe, durable and comfortable, thus providing a new route for ophthalmic drug delivery [ 6 ]. Numerous animal studies demonstrated that ophthalmic medications delivered by therapeutic contact lenses could prolong the time a drug stays on the cornea and increase its bioavailability by at least 50%, compared with eye-drop formulations [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tears also carry information and show similar glucose concentration to blood [30,52]. Tears contain organic molecules, which reflect the health status [46].…”
Section: Ocular Fluid: Tearmentioning
confidence: 99%
“…A potential way to increase the performance of prediction is by taking additional influence factors such as temperature into account. This can be carried out by sensor fusion [52,87,157]. For example, Geng et al [87] were able to improve their results significantly by combining the impedance spectroscopy-based glucose sensing system with temperature, humidity and optical sensors.…”
Section: Post-processingmentioning
confidence: 99%
“…Aside from improving the properties of commercial contact lenses or the manufacturability of contact lenses, there is also a need for advanced contact lens properties that current contact lens materials cannot fully or adequately support. Some examples of the newest contact lens advancements are ocular drug delivery via contact lenses, 11 contact lenses acting as biosensors for disease, contact lenses with advanced embedded electronics, and specialty lenses that could help patients prevent the development of myopia 12–14 . As new technologies are developed, the materials that serve as a platform for these advancements as well as knowledge of structure–property relationships must also advance.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of the newest contact lens advancements are ocular drug delivery via contact lenses, 11 contact lenses acting as biosensors for disease, contact lenses with advanced embedded electronics, and specialty lenses that could help patients prevent the development of myopia. [12][13][14] As new technologies are developed, the materials that serve as a platform for these advancements as well as knowledge of structure-property relationships must also advance. Thus, there is a significant need for the study and development of new silicone monomers and macromers and more robust silicone hydrogel formulations-mixtures that can handle the addition of new components or molecules without disrupting the oftendelicate balance of hydrophilic and hydrophobic phases and associated polymer phase morphology that affects lens properties.…”
Section: Introductionmentioning
confidence: 99%